2014
DOI: 10.1021/la500479e
|View full text |Cite
|
Sign up to set email alerts
|

Geometry-Induced Asymmetric Capillary Flow

Abstract: When capillary flow occurs in a uniform porous medium, the depth of penetration is known to increase as the square root of time. However, we demonstrate in this study that the depth of penetration in multi-section porous layers with variation in width and height against the flow time is modified from this diffusive-like response, and liquids can pass through porous systems more readily in one direction than the other. We show here in a model and an experiment that the flow time for a negative gradient of cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…The procedure has been used in previous works to calculate the filling dynamics of porous substrates with different geometrical shapes. [16][17][18][19] It should be observed that we are reporting here a general formulation of the problem, which comprises the fluid imbibition of homogeneous porous media whose cross-sectional shape ‫)ݔ(ܣ‬ may vary in one, two or three dimensions, provided the flow is unidirectional. In what follows we describe typical examples of each case, on the base of specifically shaped paper sheets, as shown schematically in Table 1.…”
Section: Direct Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure has been used in previous works to calculate the filling dynamics of porous substrates with different geometrical shapes. [16][17][18][19] It should be observed that we are reporting here a general formulation of the problem, which comprises the fluid imbibition of homogeneous porous media whose cross-sectional shape ‫)ݔ(ܣ‬ may vary in one, two or three dimensions, provided the flow is unidirectional. In what follows we describe typical examples of each case, on the base of specifically shaped paper sheets, as shown schematically in Table 1.…”
Section: Direct Calculationmentioning
confidence: 99%
“…Paper sheets with different shapes have been proposed to pump fluids with a specific dynamics: circular, 13 rectangular, 14 trapezoidal, 15 sector-shaped, 16 and different combinations of them. [14][15][16][17] In most of the studies cited above, calculations to predict the instantaneous position of the meniscus in the substrate consider a geometrical shape designed beforehand. The procedure is also used in the analysis of capillary imbibition of porous materials other than paper, 18,19 and it is a direct calculation from a mathematical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The manipulated capillary flow in non-uniform porous structures, in terms of the evolution of flow distance to time, deviates from the classical Washburn equation based on uniform tubes (Reyssat et al, 2008(Reyssat et al, , 2009Shou et al, 2014bShou et al, , 2014c. As well, the fastest capillary flow on the basis of Newtonian fluids has been found in the optimally designed tubes and porous systems (Shou and Fan, 2015;Shou et al, 2014bShou et al, , 2014cShou et al, , 2014d. However, to our best of knowledge, less studies concern the development and optimization of the fast capillary-driven power-law fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the introduction of nanofibers into the nonwovens is often utilized in strengthening the speed by enhancing the surface area. 6,7 Heterogeneous nonwovens, which were characterized with the branched networks made of micro-nanofibers, have been studied widely. [8][9][10][11] The branched network structure is common in nature, such as the vascular systems of animals, rivers, trees, and leaf veins of plants.…”
Section: Introductionmentioning
confidence: 99%